CFT+ With a Subsequent Interdisciplinary Pain Management Program (IPMP) If Needed Versus IPMP Alone for Patients With Severe Disabling Chronic LBP: Pragmatic Patient-Blinded RCT With Economic Analysis - Henrik Bjarke Vaegter; Anne Smith; Jannick Vaaben Johansen; Irene Stegemejer; Kira Søndberg Fuglsang; Jesper Fredslund Pedersen; Liza Sopina; Rob Schutze; Peter O’Sullivan; Peter Kent; Gitte Handberg; Francis Fatoye; et al. (Journal of Orthopaedic & Sports Physical Therapy, 2026)
OBJECTIVES: We aimed to determine whether, for patients with severely disabling chronic low back pain (cLBP), initiating care with cognitive functional therapy combined with psychologist support (CFT+) improved disability and pain, and was cost-effective compared with an interdisciplinary pain management program (IPMP) at 12 months. METHODS: We conducted a randomized controlled trial (NCT04399772) with concealed allocation, blinded patients, and intention-to-treat analysis. One hundred thirty-three adults with severely disabling cLBP, who were referred to an interdisciplinary pain center, were randomized to CFT+ for 3 months, with optional access to IPMP thereafter, or to IPMP alone. The primary outcome was the proportion of patients who achieved a ≥8-point improvement on the Oswestry Disability Index (ODI) at 12 months. Secondary outcomes were pain intensity, pain catastrophizing, patient enablement, global impression of change, and cost-effectiveness assessed using quality-adjusted life years (QALYs) derived from the EQ-5D-3L (EuroQol 5-Dimension 3-Level Questionnaire) and health care contacts. RESULTS: At 12 months, ODI data were available for 46 (70%) patients in the CFT+ group and 45 (67%) in the IPMP group. A ≥8-point ODI improvement was achieved by 22% of patients who received CFT+ and 18% who received IPMP (difference, 3.9%; 95% CI: −12.4%, 20.3%; P = .64). Mean ODI change did not differ between groups (difference, 0.2; 95% CI: −3.8, 4.2; P = .92). There were no significant between-group differences for the secondary outcomes. Economic analysis estimated an incremental cost-effectiveness ratio of €53 075 per QALY for CFT+ versus IPMP. CONCLUSION: CFT+ was not superior to IPMP for people with severely disabling cLBP. J Orthop Sports Phys Ther 2026;56(9):596-610. Epub 25 June 2026. doi:10.2519/jospt.2026.14238